It is zero because anything multiplied by 0 is zero
Chat with our AI personalities
(x^2)-23x=0 Start by factoring out an x: (x)(x)-23x=0 x(x-23)=0 Set each quantity to 0 and solve for x: x(x-23)=0 x=0 x-23=0 x-23+23=0+23 x=23 Therefore x=0, x=23
(5 x 1024) + (7 x 1023) + (0 x 1022) + (0 x 1021) + (0 x 1020) + (0 x 1019) + (0 x 1018) + (0 x 1017) + (0 x 1016) + (0 x 1015) + (0 x 1014) + (0 x 1013) + (0 x 1012) + (0 x 1011) + (0 x 1010) + (0 x 109) + (0 x 108) + (0 x 107) + (0 x 106) + (0 x 105) + (0 x 104) + (0 x 103) + (0 x 102) + (0 x 101) + (0 x 100)
(1 x 10000000000000000) + (0 x 1000000000000000) + (0 x 100000000000000) + (0 x 10000000000000) + (0 x 1000000000000) + (0 x 100000000000) + (0 x 10000000000) + (0 x 1000000000) + (0 x 100000000) + (0 x 10000000) + (0 x 1000000) + (0 x 100000) + (0 x 10000) + (0 x 1000) + (0 x 100) + (0 x 10) + (0 x 1)
90,000,000 can be expressed in expanded notation with and without exponents:(9 x 107) + (0 x 106) + (0 x 105) + (0 x 104) + (0 x 103) + (0 x 102) + (0 x 101) + (0 x 100).(9 x 10000000) + (0 x 1000000) + (0 x 100000) + (0 x 10000) + (0 x 1000) + (0 x 100) + (0 x 10) + (0 x 1).
x^2 - 7x = 0 x(x - 7) = 0 x = 0 or x - 7 = 0 x = 0 or x = 7